Reaching middle-income status in Ghana by 2015: What are the constraints and opportunities for raising agriculture productivity? - Benin, Samuel; Randriamamonjy, Josee (International Food Policy Research Institute, 2007)
The Government of Ghana has identified accelerated growth in agriculture as the source of its overall Growth and Poverty Reduction Strategy (GPRS II) and reaching middle-income status by 2015. Using data from the recent Ghana Living Standards Survey (GLSSV) to estimate the determinants of (i) adoption and intensity of adoption of purchased inputs, (ii) crop productivity, and (iii) agriculture income per capita, this paper analyzes the constraints and opportunities for raising agriculture production in order the above challenge... In general, increased investment in agriculture research that leads to the development of profitable technologies in local environments, increased investment in extension and other training programs to promote proper use of improved seeds, and improving the availability of improved seeds and helping farmers to acquire purchased inputs will be critical.